2007
DOI: 10.1139/x07-148
|View full text |Cite
|
Sign up to set email alerts
|

Residual-tree growth responses to partial stand harvest in the black spruce (Picea mariana) boreal forestThis article is one of a selection of papers published in the Special Forum IUFRO 1.05 Uneven-Aged Silvicultural Research Group Conference on Natural Disturbance-Based Silviculture: Managing for Complexity.

Abstract: Variants of partial harvesting are gaining favour as means to balance ecosystem management and timber production objectives on managed boreal forest landscapes. Understanding how residual trees respond to these alternative silvicultural treatments is a critical step towards evaluating their potential from either a conservation or a wood supply perspective. We used dendroecological techniques combined with a chronosequence approach to quantify the temporal radial growth response pattern of residual black spruce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 33 publications
7
16
0
Order By: Relevance
“…Age and density are essential factors in the forest structure, and influence the growth response; in our experimental treatments, we confirmed the decline in growth with age already observed in other studies [19,22,58]. In younger and denser stands (80-100 years, 2300-2900 trees/ha), radial growth response doubled that in older and open stands (110-160 years, 1300-1900 trees/ha), thus confirming hypothesis 3 ( Figure 5).…”
Section: Initial Stand Age and Densitysupporting
confidence: 91%
See 4 more Smart Citations
“…Age and density are essential factors in the forest structure, and influence the growth response; in our experimental treatments, we confirmed the decline in growth with age already observed in other studies [19,22,58]. In younger and denser stands (80-100 years, 2300-2900 trees/ha), radial growth response doubled that in older and open stands (110-160 years, 1300-1900 trees/ha), thus confirming hypothesis 3 ( Figure 5).…”
Section: Initial Stand Age and Densitysupporting
confidence: 91%
“…Older trees were also closer to their maximal height, leaving little room for vertical crown expansion after the release from lateral competition. Growth-age predictions in Thorpe et al [22] were similar to the results found in our study for older stands. However, our studied variants of shelterwood in younger stands had a higher growth response; the predictions, e.g., indicated an increase of 0.9 mm/year in 100 years old stands 9 years a.c., and we observed 0.7 and 1.6 mm/year for interior and edge trees in DS.…”
Section: Initial Stand Age and Densitysupporting
confidence: 91%
See 3 more Smart Citations